A Preliminary Study on Use of Candlenut Shell as a Renewable Source of Energy, Min Indonesia - Tambunan, B H.; Saptoadi, H.; Syamsiro, M. (Journal of Ocean, Mechanical and Aerospace -science and engineering-, 2014)
The decreased world fossil energy reserve, in general, and specifically in Indonesia requires us to find alternative energy resources. Biomass is one of alternative energies with great potential in Indonesia. One of it is Candlenuts Shell (CNS) as the waste of candlenuts fruit, with the production 89,155 tons/year will produce 207,958 tons shell/year. Candlenut shells are made into briquette with particle size < 1 mm, and then burnt in combustion test instrument with variations raw material composition of biomass and biomass charcoal. Mass reduction of each variable is measured using digital scale include RS232 that is connected to computer, burning gas temperature by using thermocouple. In terms of burning rate, generated energy and gas temperature the best raw material composition is 75% of biomass raw material and 25% of biomass charcoal.